2018
DOI: 10.1371/journal.pone.0190893
|View full text |Cite
|
Sign up to set email alerts
|

Activation of retinal glial (Müller) cells by extracellular ATP induces pronounced increases in extracellular H+ flux

Abstract: Small alterations in extracellular acidity are potentially important modulators of neuronal signaling within the vertebrate retina. Here we report a novel extracellular acidification mechanism mediated by glial cells in the retina. Using self-referencing H+-selective microelectrodes to measure extracellular H+ fluxes, we show that activation of retinal Müller (glial) cells of the tiger salamander by micromolar concentrations of extracellular ATP induces a pronounced extracellular H+ flux independent of bicarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Further experiments will be required to fully understand the role of retinal glial cells under physiological conditions and photic stimulation in the context of the entire retina. In this connection, Ca + 2 increase in MCs has been linked to ATP release (Newman, 2003), extracellular H + flux (Tchernookova et al, 2018), and potentially D -serine release (Metea and Newman, 2006), to regulate retinal neurotransmission. In addition, MCs may play a role in non-visual processes regulated by light such as the setting of the biological clock as well as in optical and visual functions acting as living optic fibers or enhancers of human vision acuity (MacDonald et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments will be required to fully understand the role of retinal glial cells under physiological conditions and photic stimulation in the context of the entire retina. In this connection, Ca + 2 increase in MCs has been linked to ATP release (Newman, 2003), extracellular H + flux (Tchernookova et al, 2018), and potentially D -serine release (Metea and Newman, 2006), to regulate retinal neurotransmission. In addition, MCs may play a role in non-visual processes regulated by light such as the setting of the biological clock as well as in optical and visual functions acting as living optic fibers or enhancers of human vision acuity (MacDonald et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular ATP also induces an increase in levels of intracellular calcium, and this calcium appears to be required for the increase in H + flux, since abolishment of ATP-induced rises in intracellular calcium using thapsigargin also eliminate the increase in H + flux measured with self-referencing H + selective electrodes. H + fluxes monitored from mouse hippocampal and rat cortical astrocytes using self-referencing electrodes have a number of features that are similar to H + fluxes previously examined from isolated retinal radial glia commonly referred to as Müller cells using similar self-referencing techniques (Tchernookova et al, 2018). Brain-derived astrocytes and retinal radial glia both display small standing H + fluxes prior to activation that are likely associated with the removal of internal H + generated by normal metabolism, and ATP applied extracellularly promotes a sizable increase in H + efflux from both cell types.…”
Section: Discussionmentioning
confidence: 69%
“…Recent experiments examining radial glial cells isolated from the vertebrate retina (Müller cells) have shown that activation of these glia by extracellular ATP induces a marked increase in extracellular H + flux, acidifying the extracellular milieu (Tchernookova et al, 2018). This ATP-induced extracellular increase in H + flux was detected from Müller cells isolated from a wide range of evolutionarily distant species, ranging from lamprey, skate, tiger salamander, rat, monkey, and human, suggesting a highly evolutionarily conserved response.…”
Section: Introductionmentioning
confidence: 99%
“…We started by analyzing the effect of purinergic receptor blockade on the size of the neurospheres formed after the culture of NPCs isolated from the SVZ of postnatal rats maintained in proliferation conditions (in the presence of EGF and FGF2). For that purpose, we used suramin at 200 µM, which is a concentration in the range of previously reported actions as a non-selective purinergic receptor antagonist [ 21 , 31 , 32 , 33 ]. The treatment of NPC cultures with suramin for 72 h induced a marked increase in the diameter of the neurospheres ( Figure 1 A–C).…”
Section: Resultsmentioning
confidence: 99%